Analgesia in the Neurosurgical Intensive Care Unit - Kvolik, Slavica; Koruga, Nenad; Skiljic, Sonja (Frontiers in Neurology, 2022)
Acute pain in neurosurgical patients is an important issue. Opioids are the most used for pain treatment in the neurosurgical ICU. Potential side effects of opioid use such as oversedation, respiratory depression, hypercapnia, worsening intracranial pressure, nausea, and vomiting may be problems and could interfere with neurologic assessment. Consequently, reducing opioids and use of nonopioid analgesics and adjuvants (N-methyl-D-aspartate antagonists, α2 -adrenergic agonists, anticonvulsants, corticosteroids), as well as nonpharmacological therapies, were introduced as a part of a multimodal regimen. Local and regional anesthesia is effective in opioid reduction during the early postoperative period. Among nonopioid agents, acetaminophen and nonsteroidal anti-inflammatory drugs are used most frequently. Adverse events associated with opioid use in neurosurgical patients are discussed. Larger controlled studies are needed to find optimal pain management tailored to neurologically impaired neurosurgical patients.